Membrane electrode, preparation method thereof and PEM electrolytic bath
By employing a porous gas diffusion layer and catalyst layer in the PEM electrolyzer, combined with a conductive structure, the problems of high catalyst dosage and poor conductivity were solved, achieving high electrolysis efficiency and long lifespan membrane electrode.
Patent Information
- Application Number
- CN202411340735.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-10
AI Technical Summary
In existing PEM electrolyzers, the catalyst dosage is high, the conductivity is poor, and the bonding performance between the catalyst and the gas diffusion layer is insufficient, which affects the electrolysis efficiency and lifespan.
A multi-level porous structure with nanoscale pores is formed by using a porous gas diffusion layer and a catalyst layer combined with a conductive structure and preparing the catalyst through alkaline etching and deposition processes. This improves the specific surface area and conductivity of the catalyst and reduces the amount of catalyst required.
It achieves high catalytic activity, low catalyst dosage, and high conductivity, thereby improving electrolysis efficiency and the antioxidant performance of the membrane electrode, and extending its service life.
Smart Images

Figure CN119287406A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of electrolytic cell manufacturing, and in particular, to a membrane electrode and a preparation method thereof, and a PEM electrolytic cell. Background Art
[0002] Proton Exchange Membrane (PEM) electrolyzer is one of the most promising green hydrogen production electrolysis technologies. Powered by renewable energy, PEM electrolyzer converts liquid water into hydrogen and oxygen without emitting carbon. At the same time, PEM electrolyzer has high integration and can operate stably under high current density conditions, greatly improving hydrogen production efficiency, high gas production pressure and faster dynamic response speed, and has great application prospects.
[0003] The core components of the PEM electrolyzer include membrane electrode, cathode plate and anode plate, among which the membrane electrode is located between the cathode plate and the anode plate. The membrane electrode is the main electrochemical reaction unit in the electrolyzer, which directly determines the working performance and hydrogen production efficiency of the electrolyzer. The membrane electrode includes a proton exchange membrane, a catalyst and a gas diffusion layer. The amount and efficiency of the catalyst can effectively promote the generation of hydrogen. Under ideal conditions, the PEM electrolyzer can exhibit a lower electrolyzer potential at a lower catalyst load, thereby improving the efficiency of water electrolysis. In addition, the cell environment of the PEM electrolyzer is mainly an acidic environment, and has a potential higher than 1.5V on the anode side. At present, the anode gas diffusion layer is mainly made of titanium material. After corrosion, the surface of the titanium material is prone to form a non-conductive oxide layer, which greatly weakens the working efficiency of the electrolyzer. At the same time, the presence of the oxide layer will reduce the bonding performance between the catalyst and the gas diffusion layer.
[0004] Therefore, there is an urgent need to develop a membrane electrode and PEM electrolyzer with high catalytic activity, low catalyst dosage and high conductivity. Summary of the invention
[0005] In view of this, the present application proposes a membrane electrode and a PEM electrolyzer, which have the advantages of high catalytic activity, low catalyst dosage and high conductivity.
[0006] In a first aspect, an embodiment of the present application provides a membrane electrode, comprising:
[0007] A proton exchange membrane and functional layers located on both sides of the proton exchange membrane, wherein the functional layers include a gas diffusion layer and a catalyst layer, wherein the catalyst layer is located between the proton exchange membrane and the gas diffusion layer, wherein both the gas diffusion layer and the catalyst layer have a porous structure, wherein the porous structure includes at least pores with a nanometer-level pore size, and wherein the material of the gas diffusion layer includes a titanium material;
[0008] A conductive structure is disposed between the gas diffusion layer and the catalyst layer, and the conductive structure exists in the form of a layered structure or a dotted structure.
[0009] In some embodiments, the dot-shaped conductive structures are embedded in pores of the gas diffusion layer and / or the catalyst layer.
[0010] In some embodiments, a ratio of a projected area of the conductive structure on the first surface to a projected area of the gas diffusion layer on the first surface is greater than or equal to 0.3, and the first surface is parallel to a surface where the gas diffusion layer is located.
[0011] In some embodiments, the conductive structure is also disposed on a side of the gas diffusion layer away from the catalyst layer.
[0012] In some embodiments, the gas diffusion layer is prepared by etching at least one of a titanium plate, a titanium mesh, and a titanium fiber felt.
[0013] In some embodiments, the average pore size of the porous structure in the gas diffusion layer is 20 nm to 20 μm.
[0014] In some embodiments, the porous structure in the gas diffusion layer includes pores with nanometer-scale pore sizes and pores with micrometer-scale pore sizes.
[0015] In some embodiments, the thickness of the gas diffusion layer is 0.1 mm to 2 mm.
[0016] In some embodiments, the porosity of the gas diffusion layer is 50% to 80%.
[0017] In some embodiments, the material of the conductive structure is selected from at least one of a single metal, an alloy, and a metal oxide.
[0018] In some embodiments, the metal element includes any one of gold, silver, ruthenium and platinum.
[0019] In some embodiments, the alloy includes at least two of gold, silver, and platinum.
[0020] In some embodiments, the metal oxide includes at least one of titanium oxide, niobium oxide, tantalum oxide, indium oxide, tin oxide, and chromium oxide.
[0021] In some embodiments, the thickness of the conductive structure is less than 50 nm.
[0022] In some embodiments, the material of the catalyst layer is selected from iridium oxide.
[0023] In some embodiments, the material of the catalyst layer is selected from at least one of iridium oxide and ruthenium oxide, titanium oxide, niobium oxide, tantalum oxide and tin oxide.
[0024] In some embodiments, the material of the catalyst layer is selected from iridium oxide and at least one of ruthenium oxide, titanium oxide, niobium oxide, tantalum oxide and tin oxide, and the mass proportion of iridium oxide in the catalyst layer is greater than or equal to 20%.
[0025] In some embodiments, the catalyst layer has a thickness of 50 nm to 5000 nm.
[0026] In some embodiments, the porosity of the catalyst layer is 5% to 80%.
[0027] In some embodiments, the iridium loading in the catalyst layer is 0.1 mg / cm 2 ~2mg / cm 2 .
[0028] In a second aspect, an embodiment of the present application provides a method for preparing a membrane electrode, comprising the following steps:
[0029] Providing a gas diffusion layer body containing titanium material, and performing alkaline etching on the gas diffusion layer body so that the gas diffusion layer body has a porous structure, wherein the porous structure at least includes pores with nanometer-level pore diameters, thereby obtaining a gas diffusion layer;
[0030] Performing a first deposition process on the gas diffusion layer to obtain a conductive structure, wherein the conductive structure exists in the form of a layer or a dot structure;
[0031] Performing a second deposition process on a surface of the conductive structure facing away from the gas diffusion layer to obtain a catalyst layer body;
[0032] Etching the catalyst layer body so that the catalyst layer body has a porous structure, wherein the porous structure at least includes pores with a nanometer-level pore size, thereby obtaining a catalyst layer, namely, a functional layer;
[0033] The functional layers are arranged on both sides of the proton exchange membrane and subjected to heat pressing treatment to obtain a membrane electrode.
[0034] In some embodiments, the alkaline solution in the alkaline etching includes at least one of sodium hydroxide and potassium hydroxide.
[0035] In some embodiments, the concentration of the alkali solution in the alkali etching is 0.1 mol / L to 10 mol / L.
[0036] In some embodiments, the temperature of the alkaline etching is 20°C to 80°C.
[0037] In some embodiments, the alkali etching time is 3 min to 120 min.
[0038] In some embodiments, the first deposition process includes at least one of atomic layer deposition, magnetron sputtering, multi-arc ion plating, and electron beam deposition.
[0039] In some embodiments, the target material of the first deposition process is selected from at least one of a metal element, an alloy, and a metal oxide, the metal element includes any one of gold, silver, ruthenium, and platinum, the alloy includes at least two of gold, silver, and platinum, and the metal oxide includes at least one of titanium oxide, niobium oxide, tantalum oxide, indium oxide, tin oxide, and chromium oxide.
[0040] In some embodiments, the deposition gas pressure of the first deposition process is 0.01Pa to 1Pa.
[0041] In some embodiments, the deposition temperature of the first deposition process is 100°C to 600°C.
[0042] In some embodiments, the target material of the second deposition process includes iridium oxide.
[0043] In some embodiments, the target material of the second deposition process includes iridium oxide and at least one of ruthenium oxide, titanium oxide, niobium oxide, tantalum oxide, and tin oxide.
[0044] In some embodiments, the second deposition process includes at least one of magnetron sputtering, multi-arc ion plating, electron beam deposition, hollow cathode deposition, and reactive sputtering.
[0045] In some embodiments, the deposition gas pressure of the second deposition process is 0.1Pa to 100Pa.
[0046] In some embodiments, the oxygen partial pressure in the second deposition process is 0.01 Pa to 10 Pa.
[0047] In some embodiments, the deposition temperature of the second deposition process is 100°C to 600°C.
[0048] In some embodiments, the etching process includes at least one of plasma etching, laser etching, and electrochemical etching.
[0049] In some embodiments, the etching process lasts for 10 seconds to 10 minutes.
[0050] In a third aspect, an embodiment of the present application provides a PEM electrolyzer, wherein the electrolyzer comprises the membrane electrode described in the first aspect.
[0051] The technical solution of this application has at least the following beneficial effects:
[0052] The membrane electrode of the present application includes a proton exchange membrane and a gas diffusion layer and a catalyst layer located on both sides of the proton exchange membrane. The gas diffusion layer and the catalyst layer both have a porous structure, and the porous structure includes at least pores with a nanometer-level pore size. The pore size of the porous structure on the gas diffusion layer and the catalyst layer of the present application is small. On the one hand, the multi-level porous structure can provide more channels, and the pores with a nanometer-level pore size help gas molecules reach the catalyst layer faster, ensure the transmission of liquid and gas in the membrane electrode, and reduce the transmission resistance; on the other hand, the catalyst layer with a porous structure can significantly increase the specific surface area of the catalyst layer, provide more active sites for the electrochemical reaction, greatly increase the contact area between the catalyst and the reactant, so that the membrane electrode can reduce the amount of catalyst under the same catalytic activity, reduce the cost of catalyst materials, and improve the catalytic efficiency and membrane electrode performance. In addition, a conductive structure is also arranged between the gas diffusion layer and the catalyst layer. The conductive structure exists in the form of a layered structure or a point structure. The conductive structure is arranged between the gas diffusion layer and the catalyst layer. On the one hand, the conductivity of the membrane electrode is improved, and on the other hand, the conductive structure can reduce the corrosion of the gas diffusion layer during long-term operation and improve the bonding performance between the gas diffusion layer and the catalyst layer. The membrane electrode of the present application has the advantages of high conductivity, high catalytic activity and low catalyst dosage.
[0053] The present application prepares a gas diffusion layer with a porous structure by pre-alkaline etching the gas diffusion layer, and then prepares a catalyst layer with a porous structure through a second deposition treatment and an etching treatment. The preparation method of the present application can prepare a membrane electrode with a multi-level porous structure with nanometer-level pore size. The pore size of the porous structure on the gas diffusion layer and the catalyst layer is relatively small. On the one hand, the multi-level porous structure can provide more channels, and the pores with nanometer-level pore size help gas molecules reach the catalyst layer faster, ensure the transmission of liquid and gas in the membrane electrode, and reduce the transmission resistance; on the other hand, the catalyst layer with a porous structure can significantly increase the specific surface area of the catalyst layer, provide more active sites for electrochemical reactions, and greatly increase the contact area between the catalyst and the reactants, so that the membrane electrode can reduce the amount of catalyst used under the same catalytic activity, reduce the cost of catalyst materials, and improve the catalytic efficiency and membrane electrode performance. In addition, after preparing the gas diffusion layer and before the catalyst layer, the process also includes: performing a first deposition process on the gas diffusion layer to obtain a conductive structure, the conductive structure exists in the form of a layer or a dot structure, and the conductive structure can improve the conductivity of the membrane electrode. At the same time, the conductive structure prepared by the first deposition can protect the gas diffusion layer, reduce the corrosion of the gas diffusion layer, and improve the oxidation resistance of the membrane electrode. At the same time, the conductive structure and the catalyst layer are both prepared by a deposition process, which can improve the bonding performance between the gas diffusion layer and the catalyst layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] In order to more clearly illustrate the embodiments of the present application or the technical solutions of the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0055] Figure 1 A flow chart of the preparation of a membrane electrode provided in an embodiment of the present application;
[0056] Figure 2 A schematic diagram of the structure of a membrane electrode provided in an embodiment of the present application;
[0057] Figure 3 A schematic diagram of the structure of another membrane electrode provided in an embodiment of the present application;
[0058] Figure 4 This is a scanning electron microscope image of the porous diffusion layer provided in Example 1 of the present application;
[0059] Figure 5 This is a scanning electron microscope image of the titanium fiber felt provided in Example 1 of the present application;
[0060] Figure 6This is a scanning electron microscope image of the catalyst layer provided in Example 1 of the present application;
[0061] Figure 7 A graph showing the contact resistance between the gas diffusion layer and the cathode plate prepared in Examples 1 to 3 and Comparative Examples 1 to 2 of the present application as a function of pressure;
[0062] Figure 8 Steady-state polarization curves of the functional layers prepared in Examples 1 to 3 and Comparative Examples 1 to 2 of the present application.
[0063] Figure 2 and Figure 3 middle:
[0064] 10- membrane electrode;
[0065] 1- Proton exchange membrane;
[0066] 2- Functional layer;
[0067] 21-gas diffusion layer;
[0068] 22-catalyst layer;
[0069] 23- Conductive structure. DETAILED DESCRIPTION
[0070] In order to better understand the technical solution of the present application, the embodiments of the present application are described in detail below with reference to the accompanying drawings.
[0071] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0072] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0073] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0074] The main components of a PEM water electrolyzer are, from the inside to the outside, the proton exchange membrane, the cathode and cathode catalyst layer, the cathode and cathode gas transmission layer, and the cathode and cathode end plates. The gas transmission layer, catalyst layer, and proton exchange membrane form the membrane electrode, which is the main site for material transmission and electrochemical reactions in the entire water electrolyzer. The characteristics and structure of the membrane electrode directly affect the performance and life of the PEM water electrolyzer. At present, the methods for preparing membrane electrodes mainly include the catalyst-coated membrane (CCM) method and the porous transport electrode (PTE) method.
[0075] In the CCM method, the catalyst is usually directly coated on both sides of the proton exchange membrane to prepare the catalyst layer. The catalyst utilization efficiency is high and the proton transport resistance between the proton exchange membrane and the catalyst layer can be reduced. However, the catalyst loading in this preparation process is too high. The amount of catalyst (such as precious metal Ir) is generally higher than 2 mg / cm 2 The preparation cost is high, and the bonding performance between the catalyst layer and the proton exchange membrane needs to be improved.
[0076] In the PTE method, the catalyst is usually directly coated on the gas diffusion layer, and then hot-pressed with the proton exchange membrane to obtain the membrane electrode. The PTE method has a simple preparation process. Since the catalyst is directly coated on the proton exchange membrane, it is beneficial to reduce the preparation cost. In addition, the catalyst and the proton exchange membrane are in close contact, and the interface resistance between the catalyst and the proton exchange membrane can be reduced, which is beneficial to improve the utilization rate of the catalyst and reduce the transmission resistance of protons, thereby improving the performance of the membrane electrode.
[0077] Whether the membrane electrode is prepared by the CCM method or the PTE method, the membrane electrode is prepared by a preparation process of slurry coating combined with high-temperature calcination. This preparation process cannot control the composition, structure and thickness uniformity of the coating. During the hot pressing process of the catalyst layer and the proton exchange membrane, the activity of the catalyst is seriously lost, resulting in a significant reduction in the utilization rate of the catalyst. In addition, the anode gas diffusion layer is currently mainly made of titanium material. After corrosion, the surface of the titanium material is prone to form a non-conductive oxide layer, which greatly weakens the working efficiency of the electrolyzer. At the same time, the presence of the oxide layer will reduce the bonding performance between the catalyst and the gas diffusion layer.
[0078] In view of this, the present application proposes a method for preparing a membrane electrode, such as Figure 1 As shown, a flow chart of preparing a membrane electrode provided in an embodiment of the present application includes the following steps:
[0079] Providing a gas diffusion layer body containing titanium material, and performing alkaline etching on the gas diffusion layer body so that the gas diffusion layer body has a porous structure, thereby obtaining a gas diffusion layer;
[0080] Performing a first deposition process on the gas diffusion layer to obtain a conductive structure, wherein the conductive structure exists in the form of a layer structure or a dot structure;
[0081] Performing a second deposition process on a surface of the conductive structure facing away from the gas diffusion layer to obtain a catalyst layer body;
[0082] Etching the catalyst layer body so that the catalyst layer body has a porous structure to obtain a catalyst layer, that is, a functional layer;
[0083] The functional layers are arranged on both sides of the proton exchange membrane and subjected to a heat pressing process to obtain a membrane electrode.
[0084] In the above scheme, the present application prepares a gas diffusion layer with a porous structure by pre-alkaline etching the gas diffusion layer containing titanium material, and then prepares a catalyst layer with a porous structure through a second deposition treatment and an etching treatment. The preparation method of the present application can prepare a membrane electrode with a multi-level porous structure, and the catalyst layer and the gas diffusion layer obtained by the etching treatment both have pores with nanometer-level pore sizes. The pore sizes of the porous structures on the gas diffusion layer and the catalyst layer of the present application are relatively small. On the one hand, the multi-level porous structure can provide more channels, and the pores with nanometer-level pore sizes help gas molecules reach the catalyst layer faster, ensure the transmission of liquid and gas in the membrane electrode, and reduce the transmission resistance; on the other hand, the catalyst layer with a porous structure can significantly increase the specific surface area of the catalyst layer, provide more active sites for the electrochemical reaction, and greatly increase the contact area between the catalyst and the reactant, so that the membrane electrode can reduce the amount of catalyst used under the same catalytic activity, reduce the cost of catalyst materials, and improve the catalytic efficiency and membrane electrode performance. In addition, after preparing the gas diffusion layer and before the catalyst layer, it also includes: performing a first deposition treatment on the gas diffusion layer to obtain a conductive structure, the conductive structure exists in the form of a layer or a point structure, and the conductive structure can improve the conductivity of the membrane electrode. At the same time, the conductive structure prepared by the first deposition can protect the gas diffusion layer and reduce the corrosion of the gas diffusion layer, thereby improving the oxidation resistance of the membrane electrode. At the same time, the conductive structure and the catalyst layer are both prepared by a deposition process, which can improve the bonding performance between the gas diffusion layer and the catalyst layer. The preparation method of the present application adopts an etching combined with a deposition process to prepare a porous and multi-level membrane electrode. Compared with the traditional coating combined with a baking process, the present application can accurately control the composition, structure and thickness uniformity of the deposited coating, thereby ensuring the stability and uniformity of the membrane electrode during batch preparation.
[0085] The preparation method of the present application is described in detail below.
[0086] S100, providing a gas diffusion layer body containing titanium material, and performing alkaline etching on the gas diffusion layer body so that the gas diffusion layer body has a porous structure, wherein the porous structure at least includes pores with nanometer-level pore diameters, thereby obtaining a gas diffusion layer.
[0087] In some embodiments, the gas diffusion layer body containing titanium material includes at least one of a titanium plate, a titanium mesh, and a titanium fiber felt. Among the above materials, the titanium mesh and the titanium fiber felt themselves have a porous structure, which is conducive to the penetration and mass transfer of the reaction gas. Preferably, the gas diffusion layer body is selected from titanium fiber felt, and the three-dimensional mesh porous structure of the titanium fiber felt not only has a high porosity, but also has a large specific surface area, which is conducive to improving the efficiency of the electrochemical reaction.
[0088] It can be understood that in the present application, the gas diffusion layer body contains or does not contain pores, and then the gas diffusion layer body is alkaline etched to further form a porous structure on the gas diffusion layer body, and the porous structure at least includes pores with nanometer-level pore sizes. Further, the porous structure includes pores with nanometer-level pore sizes and pores with micrometer-level pore sizes. The nanometer-level pores are mainly formed by alkaline etching, and the micrometer-level pores are mainly determined by the gas diffusion layer body itself (mainly titanium mesh and titanium fiber felt). In this way, the gas diffusion layer itself can also form nanopores or gradient pores formed by nanopores and micrometer pores, which greatly improves the porosity of the gas diffusion layer, improves the mass transfer efficiency, is beneficial to the subsequent deposition of the conductive structure and the catalyst layer, and improves the overall bonding performance of the membrane electrode.
[0089] In some embodiments, the alkali solution in the alkali etching includes at least one of sodium hydroxide and potassium hydroxide. The present application adopts a solution immersion method to perform alkali etching on the gas diffusion layer body, which can form a porous structure on the surface and inside of the gas diffusion layer body, which is beneficial to improve the porosity and specific surface area of the gas diffusion layer.
[0090] In some embodiments, the concentration of the alkali solution in the alkali etching is 0.1mol / L to 10mol / L, specifically 0.1mol / L, 0.5mol / L, 1mol / L, 3mol / L, 5mol / L, 8mol / L or 10mol / L, etc., and of course, it can also be other values within the above-defined range, which is not limited in this application. Controlling the concentration of the alkali solution within the above-defined range can not only ensure that the alkali solution effectively etches the porous diffusion layer body, so that more pore structures are formed on the porous diffusion layer body, especially pores with nanometer-level pores, but also avoid excessive pores on the gas diffusion layer body, which leads to a significant decrease in the mechanical properties of the gas diffusion layer body, and can achieve a balance between improving the electrochemical reaction rate of the membrane electrode and improving the service life.
[0091] In some embodiments, the temperature of the alkali etching is 20°C to 80°C, specifically 20°C, 30°C, 40°C, 50°C, 60°C, 70°C or 80°C, etc., and of course, other values within the above-defined range may also be used, which is not limited in this application. The alkali etching temperature is controlled within the above-defined range, and the alkali etching rate can be controlled, so that a suitable porous structure is formed on the gas diffusion layer body.
[0092] In some embodiments, the alkali etching time is 3 min to 120 min, specifically 3 min, 10 min, 30 min, 45 min, 60 min, 90 min or 120 min, etc. Of course, it can also be other values within the above-defined range, which is not limited in the present application.
[0093] In some embodiments, the porosity of the gas diffusion layer is 50% to 80%, specifically 50%, 55%, 60%, 65%, 70%, 75% or 80%, etc., and of course, it can also be other values within the above-defined range, which is not limited in this application. In this application, a porous structure is provided on the porous transmission layer, so that the porosity of the porous transmission layer can be selected within a wide range. Preferably, the porosity of the porous transmission layer is 60% to 80%. Within the above range, a porous transmission layer with excellent porosity can be obtained, which greatly improves the two-phase transmission rate of the existing porous transmission layer.
[0094] In some embodiments, before the alkaline etching, the process further includes: cleaning the gas diffusion layer body, specifically, using anhydrous ethanol and / or deionized water to clean the gas diffusion layer to remove impurities and contamination on the surface of the gas diffusion layer body.
[0095] In some embodiments, after the alkali etching, the method further includes: performing acid neutralization treatment on the alkali-etched product to remove excess alkali in the porous diffusion layer body. After the acid neutralization treatment, the method further includes washing and drying the gas diffusion layer body with deionized water.
[0096] In some embodiments, the acid solution in the acid neutralization treatment includes at least one of dilute hydrochloric acid and dilute nitric acid.
[0097] In some embodiments, the concentration of the acid solution is less than 0.1 mol / L, and may be specifically 0.01 mol / L, 0.03 mol / L, 0.05 mol / L, 0.08 mol / L or 0.09 mol / L, etc. Of course, it may also be other values within the above-defined range, which is not limited in this application.
[0098] In some embodiments, the time for acid neutralization treatment is 1 min to 30 min, specifically 1, 5, 10, 20 or 30, etc., and of course, it can also be other values within the above-defined range, which is not limited in this application.
[0099] S200 , performing a first deposition process on the gas diffusion layer to obtain a conductive structure, wherein the conductive structure exists in the form of a layer structure or a dot structure.
[0100] The present application performs a first deposition treatment on the gas diffusion layer, and the deposition treatment process controls the temperature, pressure, and deposition rate, etc. so that the conductive structure forms a layer structure or exists in the form of a point structure. The conductive structure of the layered structure can greatly improve the conductivity of the membrane electrode, and the existence of the conductive structure of the layered structure is conducive to the bonding between the subsequent catalyst layer and the gas diffusion layer, and improves the overall mechanical stability of the membrane electrode. The conductive structure of the point structure can not only improve the bonding force between the catalyst layer and the gas diffusion layer, but also better disperse the catalyst, increase the number of active sites, and improve the reaction efficiency of the catalyst. Moreover, the point structure can reduce the mass transfer resistance of gas and liquid, and improve the mass transfer efficiency between the subsequently formed catalyst layer and the gas diffusion layer.
[0101] In some embodiments, the first deposition process includes at least one of atomic layer deposition, magnetron sputtering, multi-arc ion plating, and electron beam deposition. Preferably, the first deposition process includes magnetron sputtering, and the magnetron sputtering process can reduce the contact resistance between the conductive structure and the gas diffusion layer. The present application does not limit the specific parameters of the above-mentioned deposition process, and those skilled in the art can set the process parameters according to the actual needs of the conductive structure.
[0102] In some embodiments, the target material of the first deposition process is selected from at least one of a metal element, an alloy, and a metal oxide.
[0103] The metal element includes any one of gold, silver, ruthenium and platinum.
[0104] The alloy includes at least two of gold, silver, ruthenium and platinum, such as a gold-silver alloy, a platinum-ruthenium alloy, and the like.
[0105] The metal oxide includes at least one of titanium oxide, niobium oxide, tantalum oxide, indium oxide, tin oxide and chromium oxide. Specifically, titanium oxide may be, for example, titanium oxide, niobium oxide may be, for example, niobium oxide, tantalum oxide may be, for example, tantalum oxide, indium oxide may be, for example, indium oxide, tin oxide may be, for example, tin oxide, chromium oxide may be, for example, chromium oxide, etc.
[0106] In some embodiments, the deposition gas pressure of the first deposition process is 0.01Pa to 1Pa, and specifically may be 0.01Pa, 0.05Pa, 0.1Pa, 0.3Pa, 0.5Pa, 0.8Pa or 1Pa, etc. Of course, it may also be other values within the above range, and the present application does not limit it here.
[0107] In some embodiments, the deposition temperature of the first deposition treatment is 100°C to 600°C, specifically 100°C, 200°C, 300°C, 400°C, 500°C or 600°C, etc. Of course, it can also be other values within the above range, which is not limited in this application.
[0108] S300, performing a second deposition process on a surface of the conductive structure facing away from the gas diffusion layer to obtain a catalyst layer body.
[0109] The second deposition treatment is performed on the surface of the conductive structure facing away from the gas diffusion layer. The present application adopts a deposition process to prepare the catalyst layer body with high purity without adding solvents and other additives. The second deposition process controls the structure, thickness and thickness uniformity of the catalyst layer body by controlling temperature, pressure and deposition rate. The preparation method is simple and can be prepared in batches.
[0110] When the conductive structure is a layered structure, the gas diffusion layer, the conductive structure and the catalyst body form a "sandwich" structure. When the conductive structure is a point structure, part of the catalyst layer body is in direct contact with the gas diffusion layer.
[0111] In some embodiments, the target material of the second deposition process may be iridium oxide, or a combination of iridium oxide and other oxides, that is, the target material of the second deposition process may also include iridium oxide and at least one of ruthenium oxide, titanium oxide, niobium oxide, tantalum oxide, and tin oxide. For example, the target material of the second deposition process may be one or more of iridium oxide, ruthenium oxide, titanium oxide, niobium oxide, tantalum oxide, or tin oxide.
[0112] In some embodiments, the second deposition process includes at least one of magnetron sputtering, multi-arc ion plating, electron beam deposition, hollow cathode deposition, and reactive sputtering. Preferably, the second deposition process includes reactive sputtering. The present application does not limit the specific parameters of the above-mentioned deposition process, and those skilled in the art can set the process parameters according to the actual needs of the catalyst body.
[0113] In some embodiments, the deposition gas pressure of the second deposition process is 0.1Pa to 100Pa, and can be specifically 0.1Pa, 0.5Pa, 1Pa, 10Pa, 30Pa, 50Pa, 80Pa or 100Pa, etc. Of course, it can also be other values within the above range, and this application is not limited thereto.
[0114] In some embodiments, the oxygen partial pressure of the second deposition treatment is 0.01Pa to 10Pa, specifically 0.01Pa, 0.05Pa, 0.1Pa, 0.5Pa, 1Pa, 5Pa or 10Pa, etc., and of course other values within the above range, which is not limited in the present application.
[0115] In some embodiments, the deposition temperature of the second deposition process is 100°C to 600°C, specifically 100°C, 200°C, 300°C, 400°C, 500°C or 600°C, etc. Of course, it can also be other values within the above range, which is not limited in this application.
[0116] S400, etching the catalyst layer body so that the catalyst layer body has a porous structure, wherein the porous structure at least includes pores with nanometer-level pore diameters, thereby obtaining a catalyst layer, namely, a functional layer.
[0117] In some embodiments, the etching process includes a plasma etching process, a laser etching process, an electrochemical etching process, and the like.
[0118] In some embodiments, the etching time is 10s to 10min, specifically 10s, 30s, 1min, 3min, 5min, 8min or 10min, etc., and of course other values within the above-defined range can also be used, which is not limited in this application. Controlling the etching time within the above-defined range can control the number and pore size of the etched holes, which is conducive to obtaining a porous structure with nanopore size, improving the porosity and specific surface area of the catalyst layer, and then controlling the number of catalyst active sites participating in the reaction, while controlling the transmission rate of liquid and gas in the catalyst layer, and obtaining a catalyst layer with high catalytic activity.
[0119] S500, disposing the functional layers on both sides of the proton exchange membrane and performing a hot pressing process to obtain a membrane electrode.
[0120] The present application also provides a membrane electrode prepared by the above method, Figure 2 A schematic diagram of the structure of a membrane electrode provided in an embodiment of the present application is shown in FIG. Figure 2 As shown, the membrane electrode 10 includes: a proton exchange membrane 1 and a functional layer 2 located on both sides of the proton exchange membrane 1, the functional layer 2 includes a gas diffusion layer 21 and a catalyst layer 22, the catalyst layer 22 is located between the proton exchange membrane 1 and the gas diffusion layer 21, the gas diffusion layer 21 and the catalyst layer 22 both have a porous structure, the porous structure includes at least pores with a nanometer-level pore size, and the material of the gas diffusion layer 21 includes a titanium material;
[0121] A conductive structure 23 is disposed between the gas diffusion layer 21 and the catalyst layer 22 . The conductive structure 23 exists in the form of a layer or a dot structure.
[0122] In the above technical scheme, the membrane electrode 10 of the present application includes a proton exchange membrane 1 and a gas diffusion layer 21 and a catalyst layer 22 located on both sides of the proton exchange membrane 1. The gas diffusion layer 21 and the catalyst layer 22 both have a porous structure, and the porous structure includes at least pores with a nanometer-level pore size. The porous structure includes at least pores with a nanometer-level pore size. The pore size of the porous structure on the gas diffusion layer 21 and the catalyst layer 22 of the present application is relatively small. On the one hand, the multi-level porous structure can provide more channels, and the pores with a nanometer-level pore size help gas molecules reach the catalyst layer faster, ensure the transmission of liquid and gas in the membrane electrode, and reduce the transmission resistance; on the other hand, the catalyst layer 22 with a porous structure can significantly increase the specific surface area of the catalyst layer 22, provide more active sites for the electrochemical reaction, and greatly increase the contact area between the catalyst and the reactant, so that the membrane electrode 10 can reduce the amount of catalyst used under the same catalytic activity, reduce the cost of catalyst materials, and improve the catalytic efficiency and membrane electrode performance. In addition, a conductive structure 23 is provided between the gas diffusion layer 21 and the catalyst layer 22. The conductive structure 23 exists in the form of a layered structure or a dotted structure. The conductive structure 23 is provided between the gas diffusion layer 21 and the catalyst layer 22. On the one hand, the conductivity of the membrane electrode 10 is improved. On the other hand, the conductive structure 23 can reduce the corrosion of the gas diffusion layer 21 during long-term operation and improve the bonding performance between the gas diffusion layer 21 and the catalyst layer 22. The membrane electrode 10 of the present application has the advantages of high conductivity, high catalytic activity and low catalyst dosage.
[0123] In the present application, the conductive structure 23 of the layered structure can greatly improve the conductivity of the membrane electrode 10, and the presence of the conductive structure 23 of the layered structure is conducive to the bonding between the subsequent catalyst layer 22 and the gas diffusion layer 11, and improves the overall mechanical stability of the membrane electrode. The conductive structure 23 of the dot structure can not only improve the bonding force between the catalyst layer 22 and the gas diffusion layer 21, but also better disperse the catalyst, increase the number of active sites, and improve the reaction efficiency of the catalyst. In addition, the dot structure can reduce the mass transfer resistance of gas and liquid, improve the mass transfer efficiency between the subsequently formed catalyst layer and the gas diffusion layer, and reduce costs at the same time.
[0124] like Figure 2 As shown, when the conductive structure 23 is a layered structure, the gas diffusion layer 21, the conductive structure 23 and the catalyst body form a "sandwich" structure. Figure 3 A schematic diagram of the structure of another membrane electrode 10 provided in an embodiment of the present application is shown in FIG. Figure 3As shown, when the conductive structure 23 is a dot-shaped structure, part of the catalyst layer 22 body is in direct contact with the gas diffusion layer 21 .
[0125] In some embodiments, the present application does not limit the shape of the porous structure of the gas diffusion layer 21 and the catalyst layer 22, and the porous structure may be, for example, a regular shape such as a column, a square, or other irregular shapes.
[0126] In some embodiments, the gas diffusion layer 21 and the catalyst layer 22 have a porous structure. When the conductive structure 23 is a point-like structure, the point-like conductive structure 23 is embedded in the pores of the gas diffusion layer 21 and / or the catalyst layer 22, which can improve the conductivity of the membrane electrode 10 without weakening the mass transfer efficiency of the membrane electrode 10. Moreover, the conductive structure 23 is arranged between the gas diffusion layer 21 and the catalyst layer 22 with a porous structure, which can effectively improve the bonding force between the gas diffusion layer 21 and the catalyst layer 22, and avoid the problem of direct contact between the porous gas diffusion layer 21 and the porous catalyst layer 22, resulting in poor mechanical stability of the membrane electrode 10.
[0127] In some embodiments, the ratio of the projected area of the conductive structure 23 on the first surface to the projected area of the gas diffusion layer 21 on the first surface is greater than or equal to 0.3, and the ratio of the projected area of the conductive structure 23 on the first surface to the projected area of the gas diffusion layer 21 on the first surface can be 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or 0.9, etc., and can also be other values within the above-defined range. The first surface is parallel to the surface where the gas diffusion layer 21 is located, and the ratio of the projected area of the conductive structure 23 on the first surface to the projected area of the gas diffusion layer 21 on the first surface is the coverage of the conductive structure 23 on the gas diffusion layer 21. The present application can improve the conductivity of the membrane electrode 10 while improving the mechanical stability of the membrane electrode 10 by controlling the coverage of the conductive structure 23 on the gas diffusion layer 21. If the coverage rate of the conductive structure 23 on the gas diffusion layer 21 is too low, the conductive performance of the membrane electrode 10 cannot be effectively improved. At the same time, a portion of the porous gas diffusion layer 21 and the porous catalyst layer 22 will be in direct contact, which may easily cause the gas diffusion layer 21 and the catalyst layer 22 to fall off.
[0128] In some embodiments, the conductive structure 23 is also disposed on a side of the gas diffusion layer 21 away from the catalyst layer 22 , that is, the conductive structure 23 is disposed on both sides of the gas diffusion layer 21 , thereby further improving the conductivity of the membrane electrode 10 .
[0129] In some embodiments, the gas diffusion layer 21 is prepared by etching at least one of a titanium plate, a titanium mesh, and a titanium fiber felt. It is understood that the gas diffusion layer 21 of the present application can be prepared by etching a titanium plate without a porous structure, and can also be prepared by etching a titanium mesh and / or a titanium fiber felt that has a porous structure.
[0130] In some embodiments, the porous structure in the gas diffusion layer includes pores with nanometer-level pore sizes and pores with micrometer-level pore sizes. It can be understood that in the gas diffusion layer, the pores with nanometer-level pore sizes are mainly formed by alkali etching, and the pores with micrometer-level pores are mainly formed by the titanium mesh or titanium fiber felt itself.
[0131] In some embodiments, the average pore size of the porous structure in the gas diffusion layer 21 is 20nm to 20μm, specifically 20nm, 50nm, 100nm, 300nm, 500nm, 1μm, 5μm, 10μm, 15μm or 20μm, etc., and of course other values within the above range can also be used, and the present application does not limit this. Within the above-mentioned limited range, the gas diffusion layer forms porous structures of different scales, wherein larger pores contribute to the transmission and drainage of gas, and smaller pores can improve the utilization rate of the catalyst layer. If the average pore size of the porous structure in the gas diffusion layer 21 is too large, the transmission efficiency of the gas between the gas diffusion layer and the catalyst layer is reduced, thereby reducing the utilization rate of the catalyst layer. If the average pore size of the porous structure in the gas diffusion layer 21 is too small, it may increase the mass transfer resistance and affect the transport of gas and water.
[0132] It can be understood that when the material of the gas diffusion layer includes titanium mesh or titanium fiber felt, the porous structure on the gas diffusion layer includes two pores of different sizes: one is the pores of the titanium mesh or titanium fiber felt itself, and the other is the pores of the titanium mesh or titanium fiber felt itself. Figure 4 This is a schematic diagram of the electron microscope of titanium fiber felt. Figure 4 In the method, holes are formed between the fibers of multiple titanium fiber felts, and the pore size is in the micron level. The other type is holes formed on the titanium mesh or titanium fiber felt by alkali etching. Figure 5 is a schematic diagram of the electron microscope of titanium fiber felt. Figure 5 As shown, the fibers of the titanium fiber felt are etched with alkali to form a pore structure, and the pore size is at the nanometer level. In some embodiments, the thickness of the gas diffusion layer 21 is 0.1 mm to 2 mm, and can be 0.1 mm, 0.3 mm, 0.8 mm, 1 mm, 1.3 mm, 1.8 mm or 2 mm, etc. Of course, it can also be other values within the above range, and this application does not limit it here.
[0133] In some embodiments, the porosity of the gas diffusion layer 21 is 50% to 80%, specifically 50%, 60%, 70% or 80%, etc., and of course other values within the above range, which are not limited in this application. The porosity of the gas diffusion layer 21 is controlled within the above-defined range, indicating that the porous diffusion layer has a high porosity and a large specific surface area, which greatly improves the permeation and mass transfer rate of gas and liquid in the membrane electrode 10.
[0134] In some embodiments, the material of the conductive structure 23 is selected from at least one of a metal element, an alloy, and a metal oxide.
[0135] The metal element includes any one of gold, silver, ruthenium and platinum.
[0136] The alloy includes at least two of gold, silver, ruthenium and platinum, such as a gold-silver alloy, a platinum-ruthenium alloy, and the like.
[0137] The metal oxide includes at least one of titanium oxide, niobium oxide, tantalum oxide, indium oxide, tin oxide and chromium oxide. Specifically, titanium oxide may be, for example, titanium oxide, niobium oxide may be, for example, niobium oxide, tantalum oxide may be, for example, tantalum oxide, indium oxide may be, for example, indium oxide, tin oxide may be, for example, tin oxide, chromium oxide may be, for example, chromium oxide, etc.
[0138] The above materials can not only improve the conductivity of the membrane electrode 10 , but also maintain a certain chemical stability during the operation of the membrane electrode 10 and are not easily corroded.
[0139] In some embodiments, the thickness of the conductive structure 23 is less than 50 nm, and can be 1 nm, 5 nm, 8 nm, 10 nm, 13 nm, 17 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm or 48 nm, etc., and can be other values within the above range, which are not limited in this application. Controlling the thickness of the conductive structure 23 within the above-defined range is beneficial to the mass transfer of the reaction medium and reduces the cost. Preferably, the thickness of the conductive structure 23 is less than 20 nm, and further preferably, the thickness of the conductive structure 23 is less than 10 nm.
[0140] In some embodiments, the material of the catalyst layer 22 is selected from iridium oxides, such as iridium oxide. As a highly efficient electrocatalyst, iridium oxide exhibits excellent catalytic activity in acidic environments and strong oxidizing environments. Moreover, iridium oxide has a high electrical conductivity, which is conducive to improving the electron transfer efficiency, thereby improving the overall electrochemical performance of the membrane electrode 10.
[0141] In some embodiments, the material of the catalyst layer 22 also includes at least one of ruthenium oxide, titanium oxide, niobium oxide, tantalum oxide and tin oxide, that is, in this embodiment, the material of the catalyst layer 22 is composed of at least two catalysts, so that the catalyst layer 22 can complement each other's advantages during use and improve the overall catalytic efficiency. Moreover, the mixed use of multiple catalysts can reduce the amount of precious metal catalysts to a certain extent and reduce costs.
[0142] In some embodiments, the mass proportion of iridium oxide in the catalyst layer 22 is greater than or equal to 20%, specifically 20%, 30%, 40%, 50%, 60%, 70% or 80%, etc., and of course other values within the above range can also be used, and the present application does not limit this. Controlling the mass proportion of iridium oxide in the catalyst layer 22 to be greater than or equal to 20% can ensure that the membrane electrode 10 has high catalytic activity.
[0143] In some embodiments, the thickness of the catalyst layer 22 is 50 nm to 5000 nm, and can be 50 nm,
[0144] 100nm, 500nm, 800nm, 1200nm, 2500nm, 3000nm, 3800nm, 4500nm or 5000nm, etc., of course, it can also be other values within the above range, and this application is not limited here.
[0145] In some embodiments, the porosity of the catalyst layer 22 is 5% to 80%, specifically 5%, 10%, 25%, 30%, 38%, 45%, 50%, 60%, 70% or 80%, etc., and of course, it can also be other values within the above range, and the present application does not limit it here. The porosity of the catalyst layer 22 is controlled within the above-defined range, indicating that the catalyst layer 22 has a high porosity and a large specific surface area, which greatly improves the catalytic activity of the membrane electrode 10 and reduces the amount of catalyst used.
[0146] In some embodiments, the iridium loading in the catalyst layer 22 is 0.1 mg / cm 2 ~2mg / cm 2 , specifically 0.1 mg / cm 2 , 0.3mg / cm 2 , 0.8mg / cm 2 , 1.2mg / cm 2 , 1.5mg / cm 2 、1.8mg / cm 2 or 2mg / cm 2 Of course, it can also be other values within the above range, and this application does not limit it. The iridium loading in the catalyst layer 22 refers to the iridium loading in any 1cm2 The mass of iridium in the region is such that if the iridium loading in the catalyst layer 22 is less than 0.1 mg / cm 2 , the catalytic ability of the membrane electrode 10 is reduced; if the iridium loading in the catalyst layer 22 is greater than 2 mg / cm 2 , the material cost is too high and the catalytic performance improvement is limited.
[0147] In this application, the porosity of each layer is tested by mercury intrusion method: the material sample is immersed in mercury, and the pressure is increased so that the mercury liquid fully penetrates the pores. The porosity can be calculated by measuring the volume of mercury pressed into the sample.
[0148] In the present application, the thickness of each layer is tested by scanning electron microscopy or by using tools such as a ruler, a caliper, a protractor, etc.
[0149] The embodiment of the present application provides a PEM electrolyzer, the PEM electrolyzer includes an anode plate and a cathode plate stacked together, a membrane electrode is arranged between the cathode plate and the anode plate, and the membrane electrode is the above-mentioned membrane electrode. Applying the membrane electrode of the present application to the PEM electrolyzer can reduce the preparation cost of the PEM electrolyzer, and at the same time has excellent material transfer performance, greatly improves the efficiency and purity of hydrogen production by electrolysis, improves the water electrolysis efficiency of the PEM electrolyzer, and can also extend the service life of the PEM electrolyzer.
[0150] The following is a further description of the embodiments of the present application in multiple embodiments. The embodiments of the present application are not limited to the following specific embodiments. Within the scope of the unchanged main rights, appropriate changes can be made to the implementation.
[0151] Example 1
[0152] (1) Provide a gas diffusion layer body titanium fiber felt, place the titanium fiber felt in anhydrous ethanol and deionized water to clean the impurities on the surface, and then use 1 mol / L sodium hydroxide to etch the surface of the titanium fiber felt to generate a porous structure. The etching temperature is 60°C and the etching time is 60 minutes. After the etching is completed, use 0.01 mol / L dilute nitric acid to clean and neutralize for 10 minutes. Finally, use deionized water to clean and dry to obtain a gas diffusion layer with a porous structure. The thickness of the gas diffusion layer is 1 mm and the porosity of the gas diffusion layer is 60%.
[0153] (2) A platinum conductive layer was deposited on the surface of the gas diffusion layer by magnetron sputtering. The deposition pressure was 0.1 Pa, the deposition temperature was 300° C., and the thickness of the platinum conductive layer was 10 nm.
[0154] (3) The iridium oxide catalytic layer body is deposited on the surface of the platinum conductive layer by an oxygen reactive sputtering method. The deposition gas pressure is 10 Pa, the oxygen partial pressure is 1 Pa, the deposition temperature is 300° C., the thickness of the iridium oxide catalytic layer body is 200 nm, and the porosity of the iridium oxide catalytic layer body is 10%.
[0155] (4) Plasma etching is used to treat the iridium oxide catalyst layer body. The etching time is 3 minutes. The porosity is adjusted to 20% to obtain a catalyst layer, that is, a functional layer.
[0156] The functional layer prepared in this embodiment includes a gas diffusion layer and a catalyst layer, the catalyst layer is located between the proton exchange membrane and the gas diffusion layer, the gas diffusion layer has pores with nanometer-level pore size and micrometer-level pore size, the porosity of the gas diffusion layer is 60%, the catalyst layer has pores with nanometer-level pore size, and the porosity of the catalyst layer is 20%. A conductive layer is arranged between the gas diffusion layer and the catalyst layer.
[0157] The electron scanning electron microscopy image of the porous diffusion layer is shown in Figure 4 and Figure 5 As shown, Figure 4 The pores in the titanium fiber felt are porous structures formed between the fibers, and the pore size is micrometer level. Figure 5 The pores in the titanium fiber felt are porous structures formed by alkali etching on the fibers, and the pore size is at the nanometer level. Figure 6 As shown, Figure 6 The pores in the catalyst layer are porous structures formed by etching the catalyst layer, and their pore sizes are at the nanometer level. Figures 4 to 6 As shown, the gas diffusion layer and the catalyst layer of the present application both have a large specific surface area, which is beneficial to improving the catalytic activity of the catalyst.
[0158] Example 2
[0159] (1) Provide a gas diffusion layer body titanium fiber felt, place the titanium fiber felt in anhydrous ethanol and deionized water to clean the impurities on the surface, and then use 1 mol / L sodium hydroxide to etch the surface of the titanium fiber felt to generate a porous structure. The etching temperature is 60°C and the etching time is 60 minutes. After the etching is completed, use 0.01 mol / L dilute nitric acid to clean and neutralize for 10 minutes. Finally, use deionized water to clean and dry to obtain a gas diffusion layer with a porous structure. The thickness of the gas diffusion layer is 1 mm and the porosity of the gas diffusion layer is 60%.
[0160] (2) A titanium oxide conductive layer is deposited on the surface of the gas diffusion layer by magnetron sputtering. The deposition pressure is 0.05 Pa, the deposition temperature is 400° C., and the thickness of the platinum conductive layer is 20 nm.
[0161] (3) The iridium oxide and ruthenium oxide catalyst layers were deposited on the surface of the platinum conductive layer by an oxygen reactive sputtering method. The deposition pressure was 5 Pa, the oxygen partial pressure was 1 Pa, the deposition temperature was 40°C, the thickness of the catalyst layer was 200 nm, the porosity of the iridium oxide catalyst layer was 10%, and the atomic ratio of iridium to ruthenium in the catalyst was 6:4.
[0162] (4) The catalyst layer body is treated by electrochemical etching for 5 min, and the porosity is adjusted to 40% to obtain a catalyst layer, that is, a functional layer.
[0163] The functional layer prepared in this embodiment includes a gas diffusion layer and a catalyst layer, the catalyst layer is located between the proton exchange membrane and the gas diffusion layer, the gas diffusion layer has pores with nanometer-level pore size and micrometer-level pore size, the porosity of the gas diffusion layer is 60%, the catalyst layer has pores with nanometer-level pore size, and the porosity of the catalyst layer is 40%. A conductive layer is arranged between the gas diffusion layer and the catalyst layer.
[0164] Example 3
[0165] (1) Provide a gas diffusion layer body titanium fiber felt, place the titanium fiber felt in anhydrous ethanol and deionized water to clean the impurities on the surface, and then use 5 mol / L sodium hydroxide to etch the surface of the titanium fiber felt to generate a porous structure. The etching temperature is 60°C and the etching time is 60 minutes. After the etching is completed, use 0.01 mol / L dilute nitric acid to clean and neutralize, and the cleaning time is 10 minutes. Finally, use deionized water to clean and dry to obtain a gas diffusion layer with a porous structure. The thickness of the gas diffusion layer is 1 mm, and the porosity of the gas diffusion layer is 80%.
[0166] (2) A dotted platinum conductive structure is deposited on the surface of the gas diffusion layer by an atomic deposition method. The deposition pressure is 0.1 Pa, the deposition temperature is 200° C., the thickness of the dotted platinum conductive structure is 10 nm, and the coverage of the dotted platinum conductive structure on the gas diffusion layer is 50%.
[0167] (3) An oxygen reactive sputtering method is used to deposit a catalyst layer of iridium oxide and titanium oxide on the surface of the point-shaped platinum conductive structure. The deposition gas pressure is 5 Pa, the oxygen partial pressure is 1 Pa, the deposition temperature is 20°C, the thickness of the catalyst layer is 500 nm, the porosity of the iridium oxide catalyst layer is 15%, and the atomic ratio of iridium to ruthenium in the catalyst body is 5:5.
[0168] (4) The catalyst layer body is treated by electrochemical etching for 5 min, and the porosity is adjusted to 60% to obtain a catalyst layer, that is, a functional layer.
[0169] The functional layer prepared in this embodiment includes a gas diffusion layer and a catalyst layer, the catalyst layer is located between the proton exchange membrane and the gas diffusion layer, the gas diffusion layer has pores with nanometer-level pore size and micrometer-level pore size, the porosity of the gas diffusion layer is 70%, the catalyst layer has pores with nanometer-level pore size, and the porosity of the catalyst layer is 60%. A platinum dot-shaped conductive structure is arranged between the gas diffusion layer and the catalyst layer, and the coverage rate of the dot-shaped platinum conductive structure on the gas diffusion layer is 50%.
[0170] Example 4
[0171] The difference from Example 1 is that in step (1), 1 mol / L sodium hydroxide is replaced by 5 mol / L sodium hydroxide.
[0172] The functional layer prepared in this embodiment includes a gas diffusion layer and a catalyst layer, the catalyst layer is located between the proton exchange membrane and the gas diffusion layer, the gas diffusion layer has pores with nanometer-level pore size and micrometer-level pore size, the porosity of the gas diffusion layer is 70%, the catalyst layer has pores with nanometer-level pore size, and the porosity of the catalyst layer is 20%. A platinum conductive layer is arranged between the gas diffusion layer and the catalyst layer.
[0173] Example 5
[0174] The difference from Example 1 is that in step (1), 1 mol / L sodium hydroxide is replaced by 10 mol / L sodium hydroxide.
[0175] The functional layer prepared in this embodiment includes a gas diffusion layer and a catalyst layer, the catalyst layer is located between the proton exchange membrane and the gas diffusion layer, the gas diffusion layer has pores with nanometer-level pore size and micrometer-level pore size, the porosity of the gas diffusion layer is 80%, the catalyst layer has pores with nanometer-level pore size, and the porosity of the catalyst layer is 20%. A platinum conductive layer is arranged between the gas diffusion layer and the catalyst layer.
[0176] Example 6
[0177] The difference from Example 1 is that the etching time in step (4) is 30 s.
[0178] The functional layer prepared in this embodiment includes a gas diffusion layer and a catalyst layer, the catalyst layer is located between the proton exchange membrane and the gas diffusion layer, the gas diffusion layer has pores with nanometer-level pore size and micrometer-level pore size, the porosity of the gas diffusion layer is 60%, the catalyst layer has pores with nanometer-level pore size, and the porosity of the catalyst layer is 10%. A platinum conductive layer is arranged between the gas diffusion layer and the catalyst layer.
[0179] Example 7
[0180] The difference from Example 1 is that the etching time in step (4) is 5 minutes.
[0181] The functional layer prepared in this embodiment includes a gas diffusion layer and a catalyst layer, the catalyst layer is located between the proton exchange membrane and the gas diffusion layer, the gas diffusion layer has pores with nanometer-level pore size and micrometer-level pore size, the porosity of the gas diffusion layer is 60%, the catalyst layer has pores with nanometer-level pore size, and the porosity of the catalyst layer is 50%. A platinum conductive layer is arranged between the gas diffusion layer and the catalyst layer.
[0182] Example 8
[0183] The difference from Example 1 is that the etching time in step (4) is 10 minutes.
[0184] The functional layer prepared in this embodiment includes a gas diffusion layer and a catalyst layer, the catalyst layer is located between the proton exchange membrane and the gas diffusion layer, the gas diffusion layer has pores with nanometer-level pore size and micrometer-level pore size, the porosity of the gas diffusion layer is 60%, the catalyst layer has pores with nanometer-level pore size, and the porosity of the catalyst layer is 80%. A platinum conductive layer is arranged between the gas diffusion layer and the catalyst layer.
[0185] Example 9
[0186] The difference from Example 3 is that in step (2), the etching time is 0.5 Pa, the deposition pressure is 0.5 Pa, the deposition temperature is 200° C., the thickness of the dotted platinum conductive structure is 20 nm, and the coverage of the dotted platinum conductive structure on the gas diffusion layer is 30%.
[0187] The functional layer prepared in this embodiment includes a gas diffusion layer and a catalyst layer, the catalyst layer is located between the proton exchange membrane and the gas diffusion layer, the gas diffusion layer has pores with nanometer-level pore size and micrometer-level pore size, the porosity of the gas diffusion layer is 70%, the catalyst layer has pores with nanometer-level pore size, and the porosity of the catalyst layer is 60%. A platinum dot-shaped conductive structure is arranged between the gas diffusion layer and the catalyst layer, and the coverage rate of the dot-shaped platinum conductive structure on the gas diffusion layer is 30%.
[0188] Example 10
[0189] The difference from Example 1 is that in step (2), the etching time is 1 Pa, the deposition pressure is 1 Pa, the deposition temperature is 300° C., the thickness of the dotted platinum conductive structure is 10 nm, and the coverage of the dotted platinum conductive structure on the gas diffusion layer is 80%.
[0190] The functional layer prepared in this embodiment includes a gas diffusion layer and a catalyst layer, the catalyst layer is located between the proton exchange membrane and the gas diffusion layer, the gas diffusion layer has pores with nanometer-level pore size and micrometer-level pore size, the porosity of the gas diffusion layer is 70%, the catalyst layer has pores with nanometer-level pore size, and the porosity of the catalyst layer is 60%. A platinum dot-shaped conductive structure is arranged between the gas diffusion layer and the catalyst layer, and the coverage rate of the dot-shaped platinum conductive structure on the gas diffusion layer is 80%.
[0191] Comparative Example 1
[0192] The difference from Example 1 is that step (1) is not performed, and the titanium fiber felt gas diffusion layer body same as that in Example 1 is directly used as the gas diffusion layer to perform steps (2) to (4).
[0193] The functional layer prepared in this comparative example includes a gas diffusion layer and a catalyst layer, the catalyst layer is located between the proton exchange membrane and the gas diffusion layer, the gas diffusion layer has pores with a micron-level pore size, the porosity of the gas diffusion layer is 50%, the catalyst layer has pores with a nanometer-level pore size, the porosity of the catalyst layer is 20%, and a platinum conductive layer is arranged between the gas diffusion layer and the catalyst layer.
[0194] Comparative Example 2
[0195] The difference from Example 1 is that step (2) is not performed.
[0196] The functional layer prepared in this comparative example includes a gas diffusion layer and a catalyst layer. The catalyst layer is located between the proton exchange membrane and the gas diffusion layer. The gas diffusion layer has pores with nanometer-level pore size and micrometer-level pore size. The porosity of the gas diffusion layer is 60%. The catalyst layer has pores with nanometer-level pore size. The porosity of the catalyst layer is 20%.
[0197] Performance measurement
[0198] The functional layers prepared in the above embodiments and comparative examples are arranged on both sides of the proton exchange membrane and hot pressed to obtain a membrane electrode, and the cathode plate (titanium plate) and the anode plate (titanium plate) are respectively placed on both sides of the membrane electrode, and the cathode plate and the gas diffusion layer, and the anode plate and the gas diffusion layer are respectively fixed by fastener bolts. The contact resistance between the cathode plate and the gas diffusion layer is measured by a contact resistance tester method.
[0199] Figure 7 The graphs of the contact resistance between the gas diffusion layer and the cathode plate prepared in Examples 1 to 3 and Comparative Examples 1 to 2 as a function of pressure are shown in FIG. Figure 7 As shown, the contact resistance of the undeposited conductive structure in Comparative Example 2 is significantly higher than that of the other four groups of samples, indicating that the conductive structure of the present application can significantly improve the conductive performance of the membrane electrode.
[0200] The functional layers prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were arranged on both sides of the proton exchange membrane and hot pressed to obtain a 25 cm 2 Small battery, test steady-state polarization curve, test temperature 60℃. Figure 8 The steady-state polarization curves of the functional layers prepared in Examples 1 to 3 and Comparative Examples 1 to 2 are as follows: Figure 8 As shown, the horizontal axis is current density and the vertical axis is voltage, that is, electrode potential. The steady-state polarization curve is an important tool for describing the kinetics of electrode processes in electrochemistry. It shows the relationship between current density and electrode potential. Under the same current density, the lower the electrode potential, the higher the catalytic activity of the catalyst.
[0201] Compared with the small batteries of Examples 1 to 3 of the present application, the small battery of Comparative Example 1 has a higher voltage at the same current density, indicating that the catalytic activity of the small battery of Comparative Example 1 is poor. The main reason is that the gas diffusion layer in Comparative Example 1 has not been subjected to alkaline etching treatment. During the operation of the small battery, the gas diffusion layer will limit the transmission of the reaction gas, thereby causing the catalytic effect of the catalyst layer to deteriorate.
[0202] Compared with the small batteries of Examples 1 to 3 of the present application, the small battery of Comparative Example 2 has a higher voltage at the same current density, and its voltage is much greater than that of the small battery of Comparative Example 1, indicating that the catalytic activity of the small battery of Comparative Example 2 is the worst. The main reason is that no conductive structure is set in Comparative Example 2. On the one hand, the conductivity of the small battery deteriorates, which limits the electron transmission efficiency in the small battery, making it impossible for the catalyst in the catalyst layer to quickly receive or transfer electrons; on the other hand, it causes the bonding performance between the porous gas diffusion layer and the porous catalyst layer to deteriorate, resulting in the transmission of the reaction gas and liquid in the catalyst layer being obstructed, reducing the reactants reaching the catalytic active sites, and reducing the catalytic reaction efficiency, thereby causing the catalytic effect of the catalyst layer to deteriorate.
[0203] In Example 1, Example 4 and Example 5, as the concentration of sodium hydroxide increases, the porosity of the gas diffusion layer increases. The porosities of Example 1, Example 4 and Example 5 are 60%, 70% and 80%, respectively. As the porosity of the gas diffusion layer increases, the larger the specific surface area of the gas diffusion layer, the better the catalytic performance.
[0204] In Example 1, Example 6, Example 7 and Example 8, as the etching time increases, the porosity of the catalyst layer increases. The porosities of Example 6, Example 1, Example 7 and Example 8 are 10%, 20%, 50% and 80%, respectively. As the porosity of the gas diffusion layer increases, the larger the specific surface area of the gas diffusion layer, the better the catalytic performance.
[0205] In Example 3, Example 9 and Example 10, the coverage of the point-shaped platinum conductive structure on the gas diffusion layer is 30%, 50% and 80% respectively. As the coverage of the point-shaped platinum conductive structure on the gas diffusion layer increases, the conductive performance becomes better.
[0206] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A membrane electrode, characterized in that: include: A proton exchange membrane and functional layers located on both sides of the proton exchange membrane, wherein the functional layers include a gas diffusion layer and a catalyst layer, wherein the catalyst layer is located between the proton exchange membrane and the gas diffusion layer, wherein both the gas diffusion layer and the catalyst layer have a porous structure, wherein the porous structure includes at least pores with a nanometer-level pore size, and wherein the material of the gas diffusion layer includes a titanium material; A conductive structure is disposed between the gas diffusion layer and the catalyst layer, and the conductive structure exists in the form of a layered structure or a dotted structure.
2. The membrane electrode according to claim 1, characterized in that: The membrane electrode further comprises at least one of the following features (1) to (3): (1) The dot-shaped conductive structure is embedded in the pores of the gas diffusion layer and / or the catalyst layer; (2) The ratio of the projected area of the conductive structure on the first surface to the projected area of the gas diffusion layer on the first surface is greater than or equal to 0.3, and the first surface is parallel to the surface where the gas diffusion layer is located; (3) The conductive structure is also disposed on a side of the gas diffusion layer away from the catalyst layer.
3. The membrane electrode according to claim 1, characterized in that: The membrane electrode further comprises at least one of the following features (1) to (5): (1) The gas diffusion layer is prepared by etching at least one of a titanium plate, a titanium mesh and a titanium fiber felt; (2) The porous structure in the gas diffusion layer includes pores with nanometer-scale pore sizes and pores with micrometer-scale pore sizes; (3) The average pore size of the porous structure in the gas diffusion layer is 20 nm to 20 μm; (4) The thickness of the gas diffusion layer is 0.1 mm to 2 mm; (5) The porosity of the gas diffusion layer is 50% to 80%.
4. The membrane electrode according to claim 1, characterized in that: The membrane electrode further comprises at least one of the following features (1) to (5): (1) The material of the conductive structure is selected from at least one of a metal element, an alloy and a metal oxide; (2) The material of the conductive structure is selected from at least one of a metal element, an alloy and a metal oxide, and the metal element includes any one of gold, silver, ruthenium and platinum; (3) The material of the conductive structure is selected from at least one of a metal element, an alloy and a metal oxide, and the alloy includes at least two of gold, silver and platinum; (4) The material of the conductive structure is selected from at least one of a metal element, an alloy and a metal oxide, and the metal oxide includes at least one of titanium oxide, niobium oxide, tantalum oxide, indium oxide, tin oxide and chromium oxide; (5) The thickness of the conductive structure is less than 50 nm.
5. The membrane electrode according to claim 1, characterized in that: The material of the catalyst layer is selected from iridium oxide; or The material of the catalyst layer is selected from at least one of iridium oxide, ruthenium oxide, titanium oxide, niobium oxide, tantalum oxide and tin oxide.
6. The membrane electrode according to claim 1, characterized in that: The membrane electrode further comprises at least one of the following features (1) to (4): (1) The material of the catalyst layer is selected from at least one of iridium oxide and ruthenium oxide, titanium oxide, niobium oxide, tantalum oxide and tin oxide, and the mass proportion of iridium oxide in the catalyst layer is greater than or equal to 20%; (2) The thickness of the catalyst layer is 50 nm to 5000 nm; (3) The porosity of the catalyst layer is 5% to 80%; (4) The iridium loading in the catalyst layer is 0.1 mg / cm 2 ~2mg / cm 2 .
7. A method for preparing a membrane electrode, characterized in that: The following steps are involved: Providing a gas diffusion layer body containing titanium material, and performing alkaline etching on the gas diffusion layer body so that the gas diffusion layer body has a porous structure, wherein the porous structure at least includes pores with nanometer-level pore diameters, thereby obtaining a gas diffusion layer; Performing a first deposition process on the gas diffusion layer to obtain a conductive structure, wherein the conductive structure exists in the form of a layer structure or a dot structure; Performing a second deposition process on a surface of the conductive structure facing away from the gas diffusion layer to obtain a catalyst layer body; Etching the catalyst layer body so that the catalyst layer body has a porous structure, wherein the porous structure at least includes pores with a nanometer-level pore size, thereby obtaining a catalyst layer, namely, a functional layer; The functional layers are arranged on both sides of the proton exchange membrane and subjected to heat pressing treatment to obtain a membrane electrode.
8. The preparation method according to claim 7, characterized in that: The preparation method comprises at least one of the following features (1) to (14): (1) The alkaline solution in the alkaline etching includes at least one of sodium hydroxide and potassium hydroxide; (2) The concentration of the alkali solution in the alkali etching is 0.1 mol / L to 10 mol / L; (3) The temperature of the alkaline etching is 20° C. to 80° C.; (4) The alkali etching time is 3 min to 120 min; (5) the first deposition process comprises at least one of atomic layer deposition, magnetron sputtering, multi-arc ion plating and electron beam deposition; (6) The target material for the first deposition process is selected from at least one of a metal element, an alloy, and a metal oxide, wherein the metal element includes any one of gold, silver, ruthenium, and platinum, the alloy includes at least two of gold, silver, and platinum, and the metal oxide includes at least one of titanium oxide, niobium oxide, tantalum oxide, indium oxide, tin oxide, and chromium oxide; (7) The deposition gas pressure of the first deposition process is 0.01Pa to 1Pa; (8) The deposition temperature of the first deposition process is 100° C. to 600° C.; (9) The target material of the second deposition process includes iridium oxide; (10) the target material of the second deposition process includes iridium oxide and at least one of ruthenium oxide, titanium oxide, niobium oxide, tantalum oxide and tin oxide; (11) the second deposition process comprises at least one of magnetron sputtering, multi-arc ion plating, electron beam deposition, hollow cathode deposition and reactive sputtering; (12) The deposition gas pressure of the second deposition process is 0.1 Pa to 100 Pa; (13) The oxygen partial pressure of the second deposition process is 0.01Pa to 10Pa; (14) The deposition temperature of the second deposition process is 100°C to 600°C.
9. The preparation method according to claim 7, characterized in that: The preparation method comprises at least one of the following features (1) to (2): (1) The etching process includes at least one of plasma etching, laser etching and electrochemical etching; (2) The etching process lasts for 10 seconds to 10 minutes.
10. A PEM electrolyzer, characterized in that: The PEM electrolyzer comprises a cathode plate and an anode substrate arranged in a stacked manner, a membrane electrode is arranged between the cathode plate and the anode plate, and the membrane electrode comprises the membrane electrode according to any one of claims 1 to 6 or a membrane electrode prepared by the method according to any one of claims 7 to 9.
Citation Information
Cited By
Coating type catalyst composite PEM electrolytic cell gas diffusion layer and preparation method thereof
CN122235752A
Gas diffusion layer, preparation method thereof and integrated reversible fuel cell
CN122393334A
Gas diffusion layer and method for producing the same, and unitized reversible fuel cell
CN122393334B